THE PECULIARITIES OF INCLUSIVE PHYSICAL EDUCATION FOR STUDENTS WITH AUTISM SPECTRUM DISORDER (Physical Culture and Sport: Scientific Perspective, 2025)
The inclusion of children with autism spectrum disorder (ASD) in school education alongside their typically developing peers is a complex, debated, and insufficiently studied issue. The implementation of inclusive education in the process of physical education, where motor activity plays a key role, is particularly controversial.Physical education specialists working in inclusive education with children with ASD indicate the challenges of involving such students in joint physical exercise activities that require interaction among all participants in the educational process. The main reasons for these difficulties include problems with social interaction, low motivation among students with ASD, and insufficient preparedness of specialists.This study focuses on optimizing the process of engaging children with ASD in physical exercise within the framework of inclusive education. It emphasizes the need to develop specialized knowledge and skills among physical education professionals to facilitate the participation of students with ASD in joint physical activities and physical education lessons. Research Objective: The objective of our study was to develop specialized knowledge and skills among physical education specialists to facilitate the inclusion of children with autism spectrum disorder in joint physical education lessons within an inclusive education framework.To achieve this objective, the following research methods were employed: theoretical methods (synthesis, analysis, comparison), sociological methods (surveys), pedagogical observation, pedagogical experiment, mathematical statistics methodsThe study assessed physical education teachers' awareness and preparedness for working in an inclusive learning environment, particularly with students with ASD. Methodological recommendations for conducting joint physical exercise activities with children with ASD were developed and integrated into professional development courses for physical education teachers.As a result of the study, teachers' theoretical knowledge and practical skills in engaging children with ASD in joint physical exercise activities during physical education lessons improved, demonstrating the effectiveness of the developed methodological recommendations.
Keywords: students; autism spectrum disorder; physical education; inclusive learning; lesson